Open Textbooks in an Introductory Sociology Course in Canada: Student Views and Completion Rates - Heather M. Ross; Christina Hendricks; Victoria Mowat (Open Praxis, 2018)
Open educational resources (OER), including open textbooks, are free, adaptable learning resources. The integration of these materials in place of commercial textbooks allows for considerable financial savings for students and creates opportunities for more active and engaged learning. The growing interest in the use of OER at a Western Canadian university led to the chance to survey students for their feedback on using OER instead of traditional commercial textbooks. This paper focuses on the views of students in an introductory sociology course for which an instructor adopted an open textbook and otherwise left the course unchanged from when it was taught with a traditional textbook. In addition, completion rates for the offerings with the open textbook are compared to previous offerings with a commercial textbook.